English Approximant Consonants: Pronunciation Difficulties Encountered by EFL Students - Uyunnasirah Hambali; Ummi Khaerati Syam; Muhammad Reza (Journal of Development Research, 2021)
This research applied quantitative research. Quantitative is basically framed in term of using numbers, closed-end question. Quantitative research is characterized as an efficient examination of wonders by gathering quantifiable information and performing factual, scientific, or computational procedures. In collecting data, the researcher used pronunciation test as instrument in order to get the data. The items of pronunciation test consisted of a list of 120 words. Each sound consisted of 5 words. Pronunciation test was given to the respondents through asking them to pronounce the words clearly and correctly while the researcher was recorded. The result of the research data showed that the students made 1085 or 93.53% errors of substitution, 38 or 3.28% errors of omission, and 37 or 3.19% errors of addition from the total errors found. It indicated that most of the students made errors in substitution with high percentage than omission and errors of substitution had higher percentage than omission and addition. The result of the data analysis showed that there were 179 or 97.28% errors of substitution, 5 or 2.72% errors of omission, and there were no errors of addition found in pronouncing English approximant consonants. So, from all kinds of errors, most of the students made errors in substitution both fricative and approximant consonants.